Contrastive Analysis: The Existence of Bundo Kanduang in Minangkabau in the Framework of Womenomics - khairatunnisak khairatunnisak; Syihabudidin Syihabudidin (Japanese Department Faculty of Cultural Science Universitas 17 Agustus 1945 Surabaya, 2025)
This study examines the current existence of bundo kanduang in the economic sector through the lens of womenomics. Womenomics policies have enabled Japanese women, who were previously excluded from pursuing careers in the economic sector due to the influence of patriarchal culture, to gain the right to pursue careers and actively contribute to the economy. Comparatively, this aligns with the role of bundo kanduang in the economic sector in Minangkabau. However, environmental support and cultural factors, such as matriarchy and patriarchy, have led to differing impacts of women's roles in Japan and Minangkabau. This study employs a qualitative research approach. The method used is descriptive qualitative, with data collection conducted through a literature review. The primary data sources for this research include internet-based resources such as scientific journals discussing bundo kanduang and womenomics, news websites, and books addressing bundo kanduang and womenomics. The findings reveal that the economic role of bundo kanduang, analyzed through the womenomics concept, demonstrates a significant and positive impact on community economics. Bundo kanduang acts as an agent of change by improving the economy through entrepreneurial activities such as selling various handicrafts and food products. However, there are notable differences between the impact of women's roles in the economic sector in Japan and Minangkabau. The participation of bundo kanduang in Minangkabau has a relatively greater influence on improving the economy compared to the contribution of Japanese women, due to differences in social and cultural environments.